Assessing the contribution of wind and water erosion in the agro-pastoral ecotone of Northern China with 137Cs tracer technology - Hongtao Jiang; Chunrong Guo; Xiaojia Li; Wanfeng Zhang; Pengfei Du; Qiankun Guo; Yousheng Wang; Jing Wang (Scientific Reports)
Abstract This study addresses the critical ecological challenges of soil wind and water erosion in the agro-pastoral ecotone of northern China, both of which significantly contribute to soil degradation. Understanding the relative contributions of these erosion types is essential for developing effective control measures. Using the136Cs tracer method, we quantified the ratio of soil wind erosion to water erosion under varying topographic and geomorphic conditions. The results revealed that cropland has experienced the most severe erosion in recent decades. Specifically, on gentle slopes (6°–8°), the rate of water erosion exceeded wind erosion by approximately eightfold. On steeper slopes (10°–15°), this trend was even more pronounced, with water erosion surpassing wind erosion by a factor of approximately 27. These findings were corroborated by measured data from a previous study area. Overall, water erosion is the dominant process in the agro-pastoral ecotone of northern China, with wind erosion playing a secondary role. Future erosion prevention strategies should prioritize hydraulic erosion control measures, particularly on sloping cropland. Furthermore, advancing research on the compound mechanisms of wind and water erosion is imperative for developing integrated mitigation strategies, ultimately supporting the sustainable development of the region’s ecological environment.